Perancangan Sistem Informasi Manajemen Produksi Kopi Berbasis Website Menggunakan Metode Agile (Studi Kasus: PT. Sumber Kofi Lestari) - Zahrah, Alfiyah; Harits, Abdurrahman (Journal of Information Systems and Business Technology, 2026)
The rapid development of information technology has driven significant changes in production management, including in the coffee industry. PT. Sumber Kofi Lestari still faces challenges in production management that rely on manual methods, such as order recording and production data management using Microsoft Excel, which leads to recording errors and delays in data updates. To address this, a web site-based information system was developed using an Agile approach that allows for gradual and flexible development as needed. With this web -based system, PT. Sumber Kofi Lestari can monitor production progress in real-time, improve operational efficiency, and reduce errors in data recording. The system implementation is equipped with key features such as order creation, production management, and invoice generation that can be accessed by the sales team, admin, and production admin. The system implementation shows increased efficiency, reduced data errors, and ease in monitoring production, thereby increasing productivity and service quality.